Visions of cell biology : reflections inspired by Cowdry's general cytology - Matlin, Karl S.; Maienschein, Jane; Laubichler, Manfred Dietrich; Cowdry, E. V. (Edmund Vincent), 1888-1975 (Convening science., 2018)
Although modern cell biology is often considered to have arisen following World War II in tandem with certain technological and methodological advances - in particular, the electron microscope and cell fractionation - its origins actually date to the 1830s and the development of cytology, the scientific study of cells. By 1924, with the publication of Edmund Vincent Cowdry's 'General Cytology', the discipline had stretched beyond the bounds of purely microscopic observation to include the chemical, physical, and genetic analysis of cells. Inspired by Cowdry's classic, watershed work, this text collects contributions from cell biologists, historians, and philosophers of science to explore the history and current status of cell biology.